Roots of Afrikaans : selected writings of Hans den Besten - Besten, Hans den, 1948-2010 (Creole language library ;, 2012)
Hans den Besten (1948-2010) made numerous contributions to Afrikaans linguistics over a period of nearly three decades. His writings helped shift the perspective on the roots of Afrikaans beyond Dutch: to the structure and vocabulary of Khoekhoen, to Portuguese Creole, and to Malay varieties. This volume contains a selection of Den Besten's most important papers concerning the structure and history of Afrikaans, covering a wide range of topics, including grammatical structure, vocabulary, the historical development of Afrikaans, as well its multiple roots.